Content validity and cognitive testing in the development of a motivational interviewing self-assessment questionnaire - Hočevar, Tadeja (Zdravstveno varstvo, 2024)
Aim: To develop and content validate a self-assessment questionnaire on motivational interviewing (MI) practice as the first stages in forming the questionnaire to be used in cross-sectional studies involving practitioners conducting the MI-based alcohol screening and brief intervention (ASBI). Methods: A comprehensive mixed methods approach included a literature review, 3 rounds of expert panel (EP) opinions (n=10), cognitive testing (CT) with 10 MI-based ASBI practitioners, and questionnaire piloting with 31 MI-based ASBI practitioners. Based on the EP opinions in the second round, content validity indices (CVIs) and the modified kappa coefficient (k*) were calculated, focusing on the relevance and understandability of questions and comprehensiveness and meaningfulness of the response options. This analysis was performed in 2020, at the conclusion of the national “Together for a Responsible Attitude Towards Alcohol Consumption” (“Skupaj za odgovoren odnos do pitja alkohola”, SOPA) project’s pilot implementation. Results: On a scale level, CVI values based on universal agreement for the entire questionnaire were high for 3/4 categories (S-CVI-UA>0.80), and CVI values based on average agreement were high across all categories (S-CVI-Ave>0.90). At the item level, CVI values (I-CVI) were never <0.50 (automatic item rejection), and the modified kappa value (k*) indicated poor validity for two items in the understandability category (k*=0.33). All problematic parts of the questionnaire were further tested and successfully modified based on the results of CT, and accepted in the third round of testing. Conclusions: The final version of the questionnaire demonstrated appropriate content validity for use in studies among Slovenian MI-based ASBI practitioners and is now ready for further psychometric testing.
Keywords: alcohol screening and brief intervention; cognitive testing; content validity; kognitivno testiranje; kratko svetovanje za opuščanje tveganega in škodljivega pitja alkohola; motivacijski intervju; motivational interviewing; samo-ocenjevalni vprašalnik; self-assessment questionnaire; vsebinska veljavnost